Genetic depletion of Soat2 diminishes hepatic steatosis via genes regulating de novo lipogenesis and by GLUT2 protein in female mice. Issue 7 (July 2019) - Ahmed, O.; Pramfalk, C.; Pedrelli, M.; Olin, M.; Steffensen, K.R.; Eriksson, M.; Parini, P.
Abstract: Depletion of the cholesterol esterifying enzyme acyl-Coenzyme A: cholesterol acyltransferase 2 (ACAT2, encoded by Soat2) protects mice from atherosclerosis, diet-induced hypercholesterolemia, and hepatic steatosis when fed high-cholesterol diet. The glucose transporter 2 (GLUT2) represents the main gate of glucose uptake by the liver. Lipid synthesis from glucose ( de novo lipogenesis; DNL) plays a pivotal role in the development of hepatic steatosis. Inhibition of DNL is a successful approach to reverse hepatic steatosis, as shown by different studies in mice and humans. Here we aimed to investigate whether depletion of Soat2 per se can reduce hepatic steatosis, also in the presence of very low levels of cholesterol in the diet, and the underlying mechanisms. Female Soat2−/− and wild type mice were either fed high-fat or high-carbohydrate diet and both contained <0.05% (w/w) cholesterol. Analysis in serum, liver, muscles and adipose tissues were performed. We found Soat2−/ − mice fed high-fat, low-cholesterol diet to have less hepatic steatosis, decreased expression of genes involved in DNL and lower hepatic GLUT2. Similar findings were found in Soat2-/- mice fed high-carbohydrate, low-cholesterol diet. Conclusion: Depletion of Soat2 reduces hepatic steatosis independently of the presence of high levels of cholesterol in the diet. Our study provides a link between hepatic cholesterol esterification, DNL, and GLUT2.